Energy Conversion of Industrial Wastewater on Microbial Fuel Cell (MFC)-Based with Biocatalysts and Pretreatments: A Review - Suryawan, I Wayan Koko; Septiariva, Iva Yenis; Sarwono, Ariyanti (Indonesian Journal of Environmental Management and Sustainability, 2020)
The purpose of this review is to provide current information regarding industrial wastewater treatment with MFC technology with the addition of biocatalysts and pretreatments. Moreover, this review also updates industrial waste treatment technology with MFC technology in Indonesia. Waste could be generated from domestic activities as well as non-domestic activities, such as industries. Industries produce waste with quite high organic content. This organic material is not easily degraded in biological treatment. Wastewater treatment, currently, aims only to meet standards quality and not to reuse. In Indonesia, the reuse processes, one of which is still rarely found in the form of energy. Industries that can process and convert wastewater energy can help the government realize sustainable development in the energy sector. One of the technologies is the Microbial Fuel Cell (MFC). Previous MFC research that had been carried out was limited to laboratory scale with a volume of less than 1 L and, among them, used mixed or artificial waste. MFC processing uses anode in wastewater as a substrate source and generates electrons under anaerobic conditions. Electron formation could be accelerated by adding biocatalysts such as enzymes and specific microorganisms. The processing occurred in an anaerobic anode that could be increased by increasing the substrate's biodegradability value in the waste. The biodegradability value can be increased by pretreatment with ozone or ultrasonic technology. In Indonesia, research on industrial wastewater treatment with MFC as well as biocatalyst and pretreatment is still relatively minimal.